Aerobic exercise training induces metabolic benefits in rats with metabolic syndrome independent of dietary changes (Clinics, 2013)
OBJECTIVES: We evaluated the effects of aerobic exercise training without dietary changes on cardiovascular and metabolic variables and on the expression of glucose transporter Type 4 in rats with metabolic syndrome. METHODS: Twenty male spontaneously hypertensive rats received monosodium glutamate during the neonatal period. The animals were allocated to the following groups: MS (sedentary metabolic syndrome), MS-T (trained on a treadmill for 1 hour/day, 5 days/week for 10 weeks), H (sedentary spontaneously hypertensive rats) and H-T (trained spontaneously hypertensive rats). The Lee index, blood pressure (tail-cuff system), insulin sensitivity (insulin tolerance test) and functional capacity were evaluated before and after 10 weeks of training. Glucose transporter Type 4 expression was analyzed using Western blotting. The data were compared using analysis of variance (ANOVA) (p